Evolution of HRM Strategies in the Digital Age: A Comprehensive Review - Sjamsier Husen; Risma Nur Wahidah; Duta Mustajab (Amkop Management Accounting Review (AMAR), 2024)
This study explores the evolution of HRM strategies in the digital age, focusing on integrating technology, data-driven decision-making, employee experience and engagement, and the impact on organizational culture and change management. We used a qualitative research approach to conduct semi-structured interviews and focus groups with HR professionals, managers, and employees from various industries. The data was analyzed using thematic analysis to identify patterns and insights related to digital HRM strategies. The study reveals that e-HRM systems and AI technologies significantly enhance HR efficiency and strategic capabilities. Personalized development programs and flexible work arrangements, supported by digital tools, improve employee experience, engagement, and retention. Effective leadership is critical in fostering a culture of adaptability and continuous learning, essential for successful digital transformation. The findings align with transformational leadership theory and highlight the importance of data-driven decision-making in modern HRM practices. The research contributes to both academic knowledge and practical application. Organizations can enhance their HRM strategies by investing in digital tools, fostering flexible work environments, and promoting continuous learning and adaptability through strong leadership. These strategies can lead to higher employee satisfaction, engagement, and organizational performance. Future research should include a broader range of organizations and longitudinal studies further to understand the long-term impacts of digital HRM strategies and explore potential challenges in digital transformation. This study provides a comprehensive framework for leveraging digital advancements in HRM to achieve optimal outcomes.